Wearable Electrospun Nanofibrous Sensors for Health Monitoring - Nonsikelelo Sheron Mpofu; Tomasz Blachowicz; Andrea Ehrmann; Guido Ehrmann (Micro)
Various electrospinning techniques can be used to produce nanofiber mats with randomly oriented or aligned nanofibers made of different materials and material mixtures. Such nanofibers have a high specific surface area, making them sensitive as sensors for health monitoring. The entire nanofiber mats are very thin and lightweight and, therefore, can be easily integrated into wearables such as textile fabrics or even patches. Nanofibrous sensors can be used not only to analyze sweat but also to detect physical parameters such as ECG or heartbeat, movements, or environmental parameters such as temperature, humidity, etc., making them an interesting alternative to other wearables for continuous health monitoring. This paper provides an overview of various nanofibrous sensors made of different materials that are used in health monitoring. Both the advantages of electrospun nanofiber mats and their potential problems, such as inhomogeneities between different nanofiber mats or even within one electrospun specimen, are discussed.